(untitled) (International Journal of Biomedical Research, 2017)
Objectives : 1) To determine the proportion of treatment compliance among hypertensive study participants. 2) To identify social demographic factors that affect treatment compliance among hypertensive study participants. Methodology: Study was descriptive cross- sectional design, which was conducted in K.I.M.S. Hubli. The study population was hypertensive patients who are on antihypertensives, attended the medicine OPD. A total of 253 patients were included in the study and the study used simple random sampling. Data were analyzed using SPSS software. P ?0.05 was considered statistical significant. Results: 160 (63.2%) participants had good compliance and 93 (36.8%) participants had poor compliance to treatment. Patients with formal education level had high good compliance (61.9%) compared to those without education (20.6%). Employed were more compliant (70%) compared with unemployed (28.1%). Participants on 2 antihypertensives were more compliant (58.8%) than participants on single or >2 antihypertensives. Participants without alcohol consumption were more compliant (85%) than who consumes alcohol. Participants who received advice from treating doctor were more compliant (81.9%) than participants without advice. Conclusions and Recommendation: This study showed low compliance to antihypertensive treatment. It is recommended that hypertensive patients should be counseled regularly to improve the compliance to antihypertensive drugs.